Coping strategies and adherence in people with mood disorder: a cross-sectional study - Jeżuchowska, Alicja; Schneider-Matyka, Daria; Rachubińska, Kamila; Reginia, Artur; Panczyk, Mariusz; Ćwiek, Dorota; Grochans, Elżbieta; Cybulska, Anna Maria (Frontiers in Psychiatry, 2024)
Non-adherence to treatment recommendations is a significant problem, as it contributes to the progression of the disease and to the exacerbation of distressing symptoms. Failure to cope with the disease and elevated levels of stress, in turn, influence the choice of strategy for coping with a difficult situation, and thus adherence to recommendations. Objectives: The purpose of our study was to evaluate the impact of the subjects’ stress coping styles on therapeutic adherence, life satisfaction, disease acceptance and quality of life (QoL) in people with mood disorders. Methods: This survey-based study included 102 respondents diagnosed with mood disorders, living in the West Pomeranian Voivodeship. It was performed using the sociodemographic questionnaire and standardized tools: The Coping Inventory for Stressful Situations (CISS), The Satisfaction with Life Scale (SWLS), The Short Form-36 (SF-36) Health Survey, The Adherence to Refills and Medication Scale (ARMS), and The Acceptance of Illness Scale (AIS). Results: Some 47.06% of the respondents suffered from depressive disorders, while 34.31% had depression or mixed anxiety disorder. Patients who made greater use of an emotion-focused style were found to have significantly lower life satisfaction than other patients. Moreover, this style was related to such SF-36 domains as general health, social functioning, role emotional, vitality, and mental health, as well as to physical component summary (PCS) and mental component summary (MCS). Conclusion: Treatment non-adherence is a serious challenge in the treatment of patients with mood disorders. Individuals who do not adequately follow treatment recommendations often resort to alternative activities as a mechanism for coping with difficult situations. Patients who predominantly adopt an emotion-oriented coping style tend to experience lower life satisfaction and greater difficulty accepting their condition compared to their peers. Conversely, patients who adopt a task-oriented coping style report better quality of life than those who rely on emotion-oriented coping or alternative activities.